2021
DOI: 10.3390/children8100830
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Cohort Study on Quality of Life among the Pediatric Population after Surgery for Recurrent Patellar Dislocation

Abstract: Patellofemoral instability is a frequent cause of knee pathology affecting quality of life among the pediatric population. Here, we present a prospective cohort study which included patients who had undergone surgical management using the lateral release and medial imbrication approach (LRMI) or medial patellofemoral ligament reconstruction (MPFL-R). The object of this study was to assess the quality of life among children that have undergone surgical treatment for patellar dislocation. Quality of life was ass… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…It consists of 19 questions about knee symptoms, function and impact on physical activities. This survey has been extensively used in the literature, [11][12][13][14][15] and a recently published systematic review showed that Pedi-IKDC is the most studied PROM and has the best psychometric properties and, as such, should be preferred in detriment of other instruments. 12 The Pedi-IKDC was already validated in many other languages, [15][16][17] with the validation studies being conducted in pediatric populations affected by a broad spectrum of knee injuries and disorders.…”
Section: Introductionmentioning
confidence: 99%
“…It consists of 19 questions about knee symptoms, function and impact on physical activities. This survey has been extensively used in the literature, [11][12][13][14][15] and a recently published systematic review showed that Pedi-IKDC is the most studied PROM and has the best psychometric properties and, as such, should be preferred in detriment of other instruments. 12 The Pedi-IKDC was already validated in many other languages, [15][16][17] with the validation studies being conducted in pediatric populations affected by a broad spectrum of knee injuries and disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies reported significant improved QoL after iMPFLr using different methods, including EQ-5D-3L, Knee Injury and Osteoarthritis Outcome Score (KOOS), Pediatric International Knee Documentation Committee Form (Pedi-IKDC), Banff Patella Instrumentation and Short Form 12 (SF-12), but none of them mentioned psychometric effects [ 14 , 36 , 39 , 40 ]. Bouras et al used EQ-5D-3L questionnaire to evaluate the Qol after iMPFLr and noted that EQ-5D index and EQ-5D VAS significantly increased at last follow-up [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…One possible reason was the standard postoperative rehabilitation protocol adopted in this study, including rapid postoperative activities and quadriceps femoris strength training, which prevented muscle atrophy caused by immobilization. Another reason was that MPFLr and TTT were able to reestablish the normal anatomy of the knee, promote normal joint reaction forces and restore patellofemoral stability, which contributed to the relief of pain and related symptoms that affected general health conditions, including mental health [ 40 ]. Therefore, postoperative improvements in clinical evaluation, including functional outcomes, and radiological evaluation lead to the improvement of Qol.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the severity of the deformity, several surgical treatments can be taken into consideration. These include both arthroscopic and open MPFL repair or reconstruction, which have shown promising outcomes in recent studies [ 40 , 41 , 42 ]. Additionally, Fulkerson-type osteotomy has emerged as an effective approach in addressing complex cases [ 43 ].…”
Section: Primary Dislocation: Follow-upmentioning
confidence: 99%